Prospective multicenter clinical trial of immunosuppressive drug withdrawal in stable adult liver transplant recipients. Issue 5 (19th September 2013) - Benítez, Carlos; Londoño, María‐Carlota; Miquel, Rosa; Manzia, Tommaso‐Maria; Abraldes, Juan G.; Lozano, Juan‐José; Martínez‐Llordella, Marc; López, Marta; Angelico, Roberta; Bohne, Felix; Sese, Pilar; Daoud, Frederic; et al.
<x xml:space="preserve">Abstract</x> Lifelong immunosuppression increases morbidity and mortality in liver transplantation. Discontinuation of immunosuppressive drugs could lessen this burden, but the safety, applicability, and clinical outcomes of this strategy need to be carefully defined. We enrolled 102 stable liver recipients at least 3 years after transplantation in a single‐arm multicenter immunosuppression withdrawal trial. Drugs were gradually discontinued over a 6 to 9‐month period. The primary endpoint was the development of operational tolerance, defined as successful immunosuppressive drug cessation maintained for at least 12 months with stable graft function and no histopathologic evidence of rejection. Out of the 98 recipients evaluated, 57 rejected and 41 successfully discontinued all immunosuppressive drugs. In nontolerant recipients rejection episodes were mild and resolved over 5.6 months (two nontolerant patients still exhibited mild gradually improving cholestasis at the end of follow‐up). In tolerant recipients no progressive clinically significant histological damage was apparent in follow‐up protocol biopsies performed up to 3 years following drug withdrawal. Tolerance was independently associated with time since transplantation (odds ratio [OR] 1.353; P = 0.0001), recipient age (OR 1.073; P = 0.009), and male gender (OR 4.657; P = 0.016). A predictive model incorporating the first two clinical variables identified subgroups of recipients with very high (79%), intermediate (30%‐38%), and very low (0%) likelihood of successful withdrawal. Conclusion: When conducted at late timepoints after transplantation, immunosuppression withdrawal is successful in a high proportion of carefully selected liver recipients. A combination of clinical parameters could be useful to predict the success of this strategy. Additional prospective studies are now needed to confirm these results and to validate clinically applicable diagnostic biomarkers. (Hepatology 2013;58:1824–1835)